2022
DOI: 10.3389/fvets.2021.800272
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Guided Fractionation of Senna singueana and Its Potential for Development of Poultry Phytogenic Feed Additives

Abstract: There has been burgeoning interest in plant-based feed additives following restrictions placed on the use of antibiotic feed additives in many countries. Phytogenic feed additives are recommended to have a range of useful properties to support the growth and development of poultry to a similar level as that obtained by supplementing feed with antibiotics. The aim of this study was to evaluate the antibacterial, anti-lipoxygenase and antioxidant activity, and in vitro safety of fractions and isolated compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…is is in agreement with Adedoyin et al [62], who demonstrated that the essential oil of S. singueana flowers had antibacterial properties in a dosedependent manner. Our findings also agree with a study by Jambwa et al [24], which demonstrated that the ethyl acetate fraction isolated from S. singueana leaves crude extract had antibacterial effects on both Gram-positive (S. aureus) and Gram-negative (Salmonella Enteritidis and E. coli) bacterial pathogens tested.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…is is in agreement with Adedoyin et al [62], who demonstrated that the essential oil of S. singueana flowers had antibacterial properties in a dosedependent manner. Our findings also agree with a study by Jambwa et al [24], which demonstrated that the ethyl acetate fraction isolated from S. singueana leaves crude extract had antibacterial effects on both Gram-positive (S. aureus) and Gram-negative (Salmonella Enteritidis and E. coli) bacterial pathogens tested.…”
Section: Discussionsupporting
confidence: 93%
“…In this experiment, the reference, ascorbic acid, had a greater scavenging capacity of DPPH radicals with IC 50 value of 20.54 ± 2.24 µ g/ml in comparison to the plant extract, which had an IC 50 value of 47.97 ± 0.69 µ g/ml. This is in agreement with the findings of Jambwa et al [ 24 ], which demonstrated that the ethyl acetate fraction isolated from S. singueana leaves crude extract exhibited DPPH radical scavenging potential but with a lower IC 50 in comparison to the standard ascorbic.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…6 There is increasing attention to selecting feed additives for dairy cows, especially for new functional feed additives that promote health and environmental sustainability, such as extracts derived from natural plants. 7,8 Although traditional nutritional supplements play a vital role in milk synthesis, excessive intake can increase nitrogen emissions, which puts pressure on the environment and harms animal welfare. 9 Moreover, the health of the mammary gland and milk synthesis is a complex physiological process that is affected by many factors, and it is often difficult for a single nutrient to meet its overall needs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have shown that extracts of S. singueana leaves have moderate antibacterial activity against poultry pathogens, potent anti-lipoxygenase activity and powerful radical scavenging antioxidant activity (7). The bark methanol extract of S. singueana has also been reported to have remarkable hepatoprotective and anti-apoptotic properties (8), promoting further exploration of the plant for beneficial properties and potential uses.…”
Section: Introductionmentioning
confidence: 99%